Epilepsy in Korean patients with Angelman syndrome - Sung-Hee Park; Jung-Rim Yoon; Heung Dong Kim; Joon Soo Lee; Young-Mock Lee; Hoon-Chul Kang (Korean Pediatric Society, 2012)
PurposeThe aim of this study was to investigate the natural history of epilepsy and response to anti-epileptic drug treatment in patients with Angelman syndrome (AS) in Korea.MethodsWe retrospectively reviewed the clinical records of 14 patients diagnosed with epilepsy out of a total of 17 patients with a genetic diagnosis of AS. These patients were seen at the Department of Pediatric Neurology at Severance Children's Hospital from March 2005 to March 2011.ResultsFourteen (9 males and 5 females) subjects (82.3%) were diagnosed with epilepsy in AS. The most common seizure types were generalized tonic-clonic (n=9, 27%) and myoclonic (n=9, 27%), followed by atonic (n=8, 24%), atypical absence (n=4, 12%) and complex partial seizure (n=3, 9%). The most commonly prescribed antiepileptic drug (AED) was valproic acid (VPA, n=12, 86%), followed by lamotrigine (LTG, n=9, 64%), and topiramate (n=8, 57%). According to questionnaires that determined whether each AED was efficacious or not, VPA had the highest response rate and LTG was associated with the highest rate of seizure exacerbation. Complete control of seizures was achieved in 6 patients. Partial control was achieved in 7 patients, while one patient was not controlled.ConclusionEpilepsy is observed in the great majority of AS patients. It may have early onset and is often refractory to treatment. There are few reports about epilepsy in AS in Korea. This study will be helpful in understanding epilepsy in AS in Korea.